Effects of ionizing radiation and HLY78 on the zebrafish embryonic developmental toxicity. (1st January 2019) - Si, Jing; Zhou, Rong; Zhao, Baoquan; Xie, Yi; Gan, Lu; Zhang, Jinhua; Wang, Yupei; Zhou, Xin; Ren, Xiaotang; Zhang, Hong
Highlights: Activation of wnt signaling allievates carbon ion radiation induced developmental toxicity. Activation of wnt signaling has no effect on proton radiation induced developmental toxicity. Carbon ion radiation down-regulates wnt signaling to promote the apoptosis. Abstract: The health-related effects of ionizing radiation on embryonic development and their underlying mechanisms are still unclear. The aim of this study was to investigate the role of Wnt signaling in mediating the developmental toxicity induced by heavy ion and proton radiation using zebrafish embryos. Zebrafish embryos were radiated with carbon ions or protons. HLY78, an activator of the Wnt signaling pathway, was added immediately after radiation. Carbon ion radiation induced a significant increase of mortality, and activating Wnt signaling using HLY78 after radiation significantly alleviated this stress. Both carbon ion and proton radiation significantly increased malformation rates and decreased hatching rates. Supplementation with HLY78 significantly reduced the effects induced by carbon ion radiation alone. After irradiation with carbon ions, embryos showed a significant decrease in heart rate, spontaneous movement, and locomotive behavior. The expression of apoptotic genes was significantly increased, while the expression of anti-apoptotic and Wnt-related genes was significantly decreased. Supplementation with HLY78 was able to reduce these effects. However, embryos irradiated with proton radiation did not show significant changes in the expression of Wnt-related genes. The results of this study improve our understanding of the mechanisms of carbon ion radiation-induced developmental toxicity, which potentially involves the inhibition of Wnt signaling.